CAN HAPPINESS AND RESILIENCE BE CULTIVATED? EVALUATION OF A TEN WEEK PILOT WITHIN A UK HEI - Akhtar, Farrukh; Payen, Marina (PEOPLE: International Journal of Social Sciences, 2019)
This paper considers whether the traits of happiness and resilience can be cultivated within a higher education institution (HEI) setting. It does this by exploring the development, implementation and evaluation of a ten-week pilot programme carried out on staff and students within a UK university. The programme involved receiving an email every weekday for ten weeks, which covered a range of themes connected with happiness and resilience. Participants were invited to carry out daily reflections and tasks. They also had access to an online discussion page hosted on the University’s virtual learning environment (VLE), called Canvas. Both staff and students across all campuses and directorates were eligible to participate. The results indicated that participants found the structure of the programme helpful and reported greater subjective levels of happiness and resilience as a result of the project. Significance of Research: The research points to the value of HEIs developing quality enhancement measures that contribute to staff and student well-being thereby strengthening their employability and soft skills.